(untitled) - American Public Health Association (Washington DC, 1992)
This text presents significant improvements of methodology and enlarged its scope to include techniques suitable for examination of many types of samples encountered in the assessment and control of water quality and water pollution.
Keywords: Sewage,Water,Nước thải,Nước; Analysis,Analysis,Phân tích,Phân tích